Joasaph II in an Unpublished List of the Metropolitans of the Ethiopian Church - Gusarova, Ekaterina V. (Scrinium, 2016)
This article introduces new information regarding the Metropolitan Joasaph II (III) (the years of his tenure were 1770–1803). Josaph II (III), the Coptic clergyman, was the head of the Ethiopian Church for 33 years. His service coincided with the initial stage of one of the most complicated period in the history of the Ethiopian Church. This period was marked by the almost complete collapse of the Christian kingdom on the Horn of Africa. The main source comprising these data is the hitherto unknown list of the Metropolitans of Ethiopia, which contains the unique data about Joasaph II. It was discovered in an unpublished manuscript of the monastery Däbrä Damo in the province of Tǝgray in northern Ethiopia and analyzed by the present author. The result of this analysis is obvious: a modern reader receives a trustworthy portrait of this ambitious person who, in spite of his efforts was not able to terminate the long-standing schism in the Ethiopian Church. His efforts, however, left fond memories of himself among his flock.